Flame-retardant wide-temperature-range electrolyte applied to lithium ion battery

By using fluorine-substituted phosphate and carbonate co-solvent in lithium-ion battery electrolyte, an efficient SEI film is formed, which solves the flammability and compatibility problems in lithium-ion batteries, and achieves high safety, long cycle life and wide temperature range performance batteries.

CN119518092APending Publication Date: 2025-02-25NANKAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411398515.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The ester electrolytes in existing lithium-ion batteries are flammable, resulting in safety problems, and the compatibility between phosphate esters and graphite negative electrodes is poor, affecting the cycle life and stability of the battery.

Method used

Fluorine is used to replace phosphate esters to reduce the interaction force and LUMO energy level between the phosphate esters and lithium ions, improve the SEI formation ability, and add carbonate co-solvent and film-forming additives to the electrolyte to form a dense SEI film.

Benefits of technology

The high ionic conductivity of the electrolyte in a wide temperature domain is achieved, the transmission dynamics of lithium ions are improved, the cycle life of the battery is extended, and the safety and stability of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518092A_ABST
    Figure CN119518092A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant wide-temperature-range electrolyte applied to a lithium ion battery, and the electrolyte comprises a lithium salt, diethyl fluorophosphate, a carbonate cosolvent and a film-forming additive, and is applied to the lithium ion secondary battery. The used diethyl fluorophosphate has a relatively low LUMO energy level, and can generate SEI rich in inorganic components on the surface of graphite, so that the compatibility to a graphite negative electrode is improved, the coulombic efficiency of the battery is effectively improved, and the cycle life of the battery is prolonged. And the acting force between the diethyl fluorophosphate and lithium ions is weaker, so that the lithium ions can weaken the desolvation energy barrier of phosphate at the graphite negative electrode, the internal resistance of the battery is reduced, and the rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a flame retardant wide temperature range electrolyte for lithium ion batteries. Background Art

[0002] Lithium-ion batteries have received extensive attention and use over the past few decades. However, commercial lithium-ion batteries currently face severe safety challenges in large-scale applications. This is mainly because the ester electrolytes they use are highly flammable and prone to thermal runaway when the battery is subjected to collision, puncture, heating, etc., causing serious safety issues.

[0003] Adding flame retardants to the electrolyte is one of the effective means to solve the above problems. Phosphate solvents (such as trimethyl phosphate (TMP) and triethyl phosphate (TEP)) are highly favored in the field of lithium-ion batteries due to their good miscibility with carbonates, low price, low toxicity, and excellent flame retardancy. However, the strong interaction between traditional phosphate molecules and lithium ions makes it difficult for them to undergo a desolvation process at the graphite negative electrode, and a solid electrolyte interface film (SEI) film cannot be formed. This leads to continuous stripping of the electrode induced by solvent co-embedding, which seriously affects the cycle life and cycle stability of lithium-ion batteries. Therefore, the amount of phosphate used in the electrolyte is usually less than 10%, but in practical applications, the presence of a large amount of flammable solvents still poses a safety risk.

[0004] At present, the common method of making the electrolyte flame retardant and safe under the premise of ensuring the compatibility of phosphate ester and graphite negative electrode is to improve the ability of phosphate ester to form SEI film by molecular design. For example, CN 103296311 uses cyclic phosphate ester to improve the compatibility of phosphate ester and graphite negative electrode. However, the phosphate ester in this scheme still has problems such as high viscosity and low low-temperature ionic conductivity. Therefore, it is of great practical significance to promote the application of high-safety lithium-ion batteries by developing new phosphate ester molecules through molecular design to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of poor compatibility between existing phosphate molecules and graphite negative electrodes while maintaining the safety of electrolyte non-flammable batteries. By adopting the strategy of fluorine-substituted phosphate, the interaction force and LUMO energy level between phosphate and lithium ions are reduced, thereby reducing the desolvation energy barrier of phosphate and improving the SEI formation ability. At the same time, the fluorinated phosphate has a low melting point and exhibits high ionic conductivity at low temperatures, thereby improving the transmission kinetics of lithium ions and realizing long-cycle, high-safety, and wide-temperature lithium-ion batteries.

[0006] The technical solution of the present invention:

[0007] In a first aspect of the present invention, a flame retardant wide temperature range electrolyte for lithium ion batteries is provided, comprising a lithium salt, diethyl fluorophosphate, a carbonate co-solvent and a film-forming additive, wherein the structure of diethyl fluorophosphate (PF) is as follows:

[0008]

[0009] Wherein, the lithium salt is selected from one or more of lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium bis(trifluorosulfonyl)imide, and lithium perchlorate;

[0010] Wherein, the carbonate co-solvent is selected from one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate;

[0011] The film-forming additive is one or more of lithium nitrate, vinylene carbonate, and fluoroethylene carbonate.

[0012] The diethyl fluorophosphate accounts for 1-98% of the volume of the whole electrolyte; the carbonate accounts for 1-98% of the volume of the whole electrolyte; the film-forming additive accounts for 1-98% of the volume of the whole electrolyte, and the volume of the whole electrolyte is 100%.

[0013] The lithium salt concentration is 0.5-10 mol / L, preferably 1-3 mol / L, and more preferably 2 mol / L.

[0014] Preferably, the volume ratio of diethyl fluorophosphate to carbonate co-solvent and film-forming additive is 1:1:0.02 or 1:2:0.02 or 1:3:0.02, preferably 1:2:0.02.

[0015] The second aspect of the present invention provides a method for preparing the flame retardant wide temperature range electrolyte:

[0016] S1. Synthesis of diethyl fluorophosphate: diethyl phosphite and N-chlorosuccinimide are reacted in a molar ratio of 1:0.5 to 1:2 under argon protection. After the reaction is completed, suction filtration and rotary evaporation are performed to obtain a crude product of diethyl chlorophosphate. Potassium fluoride is mixed with the crude product and reacted under argon protection, and then reduced pressure distillation is performed to obtain diethyl fluorophosphate. The molar ratio of diethyl chlorophosphate to potassium fluoride is 1:1 to 1:2.

[0017] S2, mixing the dehydrated diethyl fluorophosphate, carbonate co-solvent and film-forming additive in a certain volume ratio;

[0018] S3. Add lithium salt to the mixed solvent obtained in S2, and stir to dissolve the lithium salt to obtain the flame-retardant wide temperature range electrolyte of the present invention.

[0019] Preferably, the reactants required in step S1 are 1 equivalent of diethyl phosphite and 1.1 equivalents of N-chlorosuccinimide, which are reacted under argon protection, the reaction temperature is room temperature, and the reaction time is 2-12 hours. After the reaction is completed, suction filtration and rotary evaporation are performed to obtain a crude product of diethyl chlorophosphate, which is reacted with 1.7 equivalents of potassium fluoride under argon protection, the reaction temperature is room temperature, and the reaction time is 8-16 hours. After the reaction is completed, reduced pressure distillation is performed twice, and the component evaporated at an oil bath temperature of 40°C-50°C and a Kjeldahl distillation head thermometer of 20°C-25°C is diethyl fluorophosphate.

[0020] The flame-retardant wide-temperature-range electrolyte of the present invention can be applied to lithium-ion secondary batteries. Positive electrode materials that can be matched are lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium cobalt oxide, organic lithium positive electrode, lithium-rich manganese-based positive electrode, and sulfur positive electrode.

[0021] The present invention uses diethyl fluorophosphate (DEFP) which has a weak interaction with lithium ions as a co-solvent and flame retardant for the electrolyte. Phosphorus-based flame retardants decompose to generate free radicals such as PO· and HPO·, which capture a large number of H· and OH· free radicals generated during the combustion process, thereby destroying and inhibiting the chain reaction. In addition, the flame retardant can also reduce the combustion temperature by endothermic cooling, further inhibiting the combustion process. This mechanism effectively reduces the progress of the combustion reaction, thereby improving the safety of the electrolyte. The electrolyte provided by the present invention exhibits a high ionic conductivity in the range of -40 to 60°C. Due to the weak interaction between DEFP and lithium ions and the low LUMO energy level, the desolvation energy barrier can be effectively reduced. DEFP decomposes at the electrode interface to form rich inorganic substances, and carbonates can decompose at the interface to form polymers. The two work together to form a dense, uniform, inorganic-rich SEI film with the assistance of a film-forming additive, thereby improving the ion transmission efficiency and cycle stability of the battery. Therefore, using the electrolyte provided by the present invention, the NCM811||Gr full battery still has a capacity retention rate of 84.9% after 300 cycles. At the same time, DEFP exhibits better thermal stability under the needle puncture test, greatly improving the safety of lithium-ion batteries.

[0022] Advantages and beneficial effects of the present invention:

[0023] (1) The diethyl fluorophosphate used in the present invention has a low LUMO energy level and can generate an inorganic component-rich SEI on the graphite surface, thereby improving the compatibility with the graphite negative electrode, effectively improving the coulombic efficiency of the battery, and increasing the cycle life of the battery.

[0024] (2) The interaction between the diethyl fluorophosphate used in the present invention and the lithium ions is weaker, which is beneficial for the lithium ions to weaken the desolvation energy barrier of the phosphate at the graphite negative electrode, reduce the internal resistance of the battery, and improve the rate performance of the battery.

[0025] (3) The diethyl fluorophosphate used in the present invention has a relatively low melting point and can effectively improve the performance of the electrolyte at low temperatures.

[0026] (4) The electrolyte system formed by the present invention is completely non-flammable during the ignition test, which greatly ensures the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The hydrogen nuclear magnetic spectrum of diethyl fluorophosphate of Example 1;

[0028] Figure 2 The carbon-NMR spectrum of diethyl fluorophosphate of Example 1;

[0029] Figure 3 The nuclear magnetic phosphorus spectrum of diethyl fluorophosphate of Example 1;

[0030] Figure 4 The NMR fluorine spectrum of diethyl fluorophosphate of Example 1;

[0031] Figure 5 is the ionic conductivity of the electrolyte of Example 1 in a wide temperature range of -50°C to 60°C;

[0032] Figure 6 Schematic diagram of ignition test of electrolyte of Example 1 and commercial electrolyte;

[0033] Figure 7 This is a cycle performance diagram of Li||Gr button battery assembled using the D-PF electrolyte in Example 1;

[0034] Figure 8 The cycle performance diagram of the NCM811||Gr soft pack battery assembled using the D-PF electrolyte in Example 1;

[0035] Fig. 9 This is a puncture test diagram of an NCM811||Gr soft-pack battery assembled using the D-PF electrolyte in Example 1;

[0036] Fig.10 This is a comparison chart of the cycle performance of Li||Gr button cells assembled with D-TEP and D-PF electrolytes in Comparative Example 1;

[0037] Fig.11 A comparison chart of the cycle performance of Li||Gr button cells assembled with D-without PF and D-PF electrolytes in Comparative Example 2;

[0038] Fig.12 A comparison chart of the cycle performance of Li||Gr button cells assembled with D-without DEC and D-PF electrolytes in Comparative Example 3;

[0039] Fig.13 This is a comparison chart of the cycle performance of Li||Gr button batteries assembled with D-withoutVC and D-PF electrolytes in Comparative Example 4. DETAILED DESCRIPTION

[0040] The following will further describe the phosphate flame retardant electrolyte and its preparation method and application in detail with reference to the accompanying drawings. It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present application, and do not constitute an improper limitation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as those commonly understood by ordinary technicians in the technical field to which the present application belongs.

[0041] Embodiment 1:

[0042] S1: Take 0.13 mol of diethyl phosphite and 0.14 mol of N-chlorosuccinimide in a round-bottom flask, react at room temperature for 6 hours under argon protection, filter and evaporate, then add 0.25 mol of potassium fluoride, react at room temperature for 12 hours under argon protection, and distill under reduced pressure at an oil bath temperature of 40°C-50°C and a Kjeldahl distillation head thermometer of 20°C-25°C. The component evaporated is diethyl fluorophosphate.

[0043] Figure 1 This is the H-NMR spectrum of diethyl fluorophosphate synthesized by S1. The test conditions are: 400 MHz, deuterated chloroform. The figure shows that the product has no impurity peaks and is of high purity;

[0044] Figure 2 This is the NMR carbon spectrum of diethyl fluorophosphate synthesized by S1. The test conditions are: 101MHz, deuterated chloroform. The figure shows that the product has no impurity peaks and is of high purity;

[0045] Figure 3 This is the NMR phosphorus spectrum of diethyl fluorophosphate synthesized by S1. The test conditions are: 162MHz, deuterated chloroform. The figure shows that the product has no impurity peaks and is of high purity;

[0046] Figure 4 This is the NMR spectrum of diethyl fluorophosphate synthesized by S1. The test conditions are: 376MHz, deuterated chloroform. The figure shows that the product has no impurity peaks and is of high purity;

[0047] S2 activates the molecular sieve at 450°C for 8 hours, cools the temperature to 200-160°C, adds it to the diethyl fluorophosphate solvent synthesized by S1, removes water for 48 hours, and puts it in a glove box for use; the diethyl fluorophosphate, ethylene carbonate, and diethyl carbonate after removal of water are mixed in a volume ratio of 1:1:1, 2M LiPF6 is dissolved in the mixed solvent, and then vinylene carbonate is mixed in at 2% of the total volume fraction to obtain the electrolyte D-PF.

[0048] About 1 g of the obtained electrolyte and commercial electrolyte (1M LIPF6 EC / DEC (1:1)) were soaked in a glass fiber separator and ignited for testing.

[0049] Figure 6 The results of the ignition test using the electrolyte of Example 1 and the commercial electrolyte are shown in FIG. 1 . The commercial electrolyte burns immediately and stops burning after all the electrolyte is consumed, while the electrolyte of Example 1 does not ignite at all.

[0050] 80wt% graphite active material powder, 10wt% acetylene black conductive agent and 10wt% polyvinylidene fluoride (PVDF) binder were mixed evenly, and then an appropriate amount of N-methylpyrrolidone was added to the mixed powder, and the slurry was homogenized for 30 minutes to obtain electrode slurry. The slurry was evenly applied on copper foil with a scraper, and then cut after vacuum drying at 80°C for 10 hours to obtain a graphite negative electrode. The obtained electrolyte and the obtained electrode were assembled into a Li||Gr button battery, and the cycle battery performance was tested.

[0051] Figure 7 The cycle performance diagram of D-PF electrolyte is shown in Figure 2. Figure 7 It can be seen that after 160 cycles, the capacity retention rate of D-PF is about 96.9%, and the cycle is stable.

[0052] 94wt% LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) active material powder, 2.5wt% acetylene black conductive agent (Super P) and 3.5wt% polyvinylidene fluoride binder (PVDF) are mixed evenly, and then an appropriate amount of N-methylpyrrolidone is added to the mixed powder, and the slurry is homogenized for 30 minutes to obtain an electrode slurry. In a glove box with an argon atmosphere, the slurry is evenly applied on an aluminum foil with a scraper, and cut after vacuum drying at 80°C for 10 hours to obtain a ternary material positive electrode. 95wt% of graphite active material powder, 1wt% of acetylene black conductive agent, 1.5wt% of sodium carboxymethyl cellulose (CMC) binder, and 2.5wt% of styrene butadiene latex (SBR) binder are mixed evenly, and then an appropriate amount of N-methylpyrrolidone is added to the mixed powder, and the slurry is homogenized for 30 minutes to obtain an electrode slurry. The slurry is evenly applied on a copper foil with a scraper, and cut after vacuum drying at 80°C for 10 hours to obtain a graphite negative electrode. The electrolyte obtained in Example 1 and the obtained electrode were assembled into NCM811||Gr soft pack batteries, and the cycle battery performance was tested. N / P ratio = 1 and E / C ratio = ~3.45g Ah -1 ,like Figure 8 As shown, after 100 cycles under the conditions of 0.2C charging and 0.3C discharging, the capacity retention rate is 96.1%.

[0053] The electrolyte obtained in Example 1 and the obtained electrode were assembled into NCM811||Gr soft pack batteries, and a needle puncture test was performed. Fig. 9 It can be seen that under the experimental conditions, the soft-pack battery did not catch fire or explode, proving that the use of the electrolyte in the battery ensures the safety of the battery.

[0054] Embodiment 2:

[0055] The difference from Example 1 is that the film-forming additive is replaced with lithium nitrate, and the other conditions remain unchanged. The same Li||Gr button battery as in Example 1 is assembled, and the capacity retention rate is 95.7%.

[0056] Embodiment 3:

[0057] The difference from Example 1 is that the diethyl fluorophosphate, ethylene carbonate and diethyl carbonate after dehydration are mixed in a volume ratio of 1:1:2, and the other conditions remain unchanged to assemble the same Li||Gr button battery as in Example 1, with a capacity retention rate of 94.9%.

[0058] Comparative Example 1:

[0059] Triethyl phosphate (TEP) is mixed with ethylene carbonate and diethyl carbonate in a volume ratio of 1:1:1, 2M LiPF6 is dissolved in the mixed solvent, and then vinylene carbonate is added at 2% of the total volume fraction to obtain an electrolyte D-TEP. The volume of the electrolyte D-TEP is the same as that of the electrolyte D-PF in Example 1.

[0060] The obtained electrolyte was assembled into the same Li||Gr button battery as in Example 1, and the cycle battery performance was tested. Fig.10 The comparison chart of the cycle performance of D-TEP and D-PF electrolytes is shown in Figure 2. Fig.10 It can be seen that after 160 cycles, the capacity retention rate of D-PF is higher and the cycle is more stable.

[0061] Comparative Example 2:

[0062] Ethylene carbonate and diethyl carbonate were mixed in a volume ratio of 1:1, and 1M LiPF6 was dissolved in the mixed solvent to obtain an electrolyte D-without PF. The volume of the electrolyte D-without PF was the same as that of the electrolyte D-PF in Example 1.

[0063] The obtained electrolyte was assembled into the same Li||Gr button battery as in Example 1, and the cycle battery performance was tested. Fig.11 This is a comparison chart of the cycle performance of D-without PF and D-PF electrolytes. From the figure, it can be seen that after 160 cycles, the capacity retention rate of D-PF is higher and the cycle is more stable.

[0064] Comparative Example 3:

[0065] The dehydrated diethyl fluorophosphate and ethylene carbonate were mixed in a volume ratio of 1:1, and then 2% of the total volume fraction of vinylene carbonate was added to obtain electrolyte D-without DEC. The volume of electrolyte D-without DEC was the same as that of electrolyte D-PF in Example 1.

[0066] The obtained electrolyte was assembled into the same Li||Gr button battery as in Example 1, and the cycle battery performance was tested. Fig.12 The comparison chart of the cycle performance of D-without DEC and D-PF electrolytes is shown in Figure 2. Fig.12 It can be seen that after 20 cycles, the capacity retention rate of D-PF is higher and the cycle is more stable.

[0067] Comparative Example 4:

[0068] The diethyl fluorophosphate, ethylene carbonate and diethyl carbonate after removal of water were mixed in a volume ratio of 1:1:1 to obtain an electrolyte D-without VC. The volume of the electrolyte D-without VC was the same as that of the electrolyte D-PF in Example 1.

[0069] The obtained electrolyte was assembled into the same Li||Gr button battery as in Example 1, and the cycle battery performance was tested. Fig.13 This is a comparison chart of the cycle performance of D-without VC and D-PF electrolytes. It can be seen from the figure that after 20 cycles, the capacity retention rate of D-PF is higher and the cycle is more stable.

[0070] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A flame retardant wide temperature range electrolyte for lithium ion batteries, characterized in that: It includes lithium salt, diethyl fluorophosphate, carbonate co-solvent and film-forming additive, wherein the structure of diethyl fluorophosphate is as follows: The carbonate co-solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; The film-forming additive is one or more of lithium nitrate, vinylene carbonate, and fluoroethylene carbonate; The lithium salt concentration is 0.5-10 mol / L, the diethyl fluorophosphate accounts for 1-98% of the total electrolyte volume; the carbonate accounts for 1-98% of the total electrolyte volume; the film-forming additive accounts for 1-98% of the total electrolyte volume, and the total electrolyte volume is 100%.

2. The flame retardant wide temperature range electrolyte for lithium ion batteries according to claim 1, characterized in that: The lithium salt is one or more of lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium bis(trifluorosulfonyl)imide and lithium perchlorate.

3. The flame retardant wide temperature range electrolyte for lithium ion batteries according to claim 2, characterized in that: The lithium salt concentration is 1-3 mol / L.

4. The flame retardant wide temperature range electrolyte for lithium ion batteries according to claim 1, characterized in that: The volume ratio of diethyl fluorophosphate to carbonate co-solvent and film-forming additive is 1:1:0.02 or 1:2:0.02 or 1:3:0.

02.

5. The flame retardant wide temperature range electrolyte for lithium ion batteries according to claim 1, characterized in that: Applied to lithium-ion secondary batteries, the positive electrode materials matched with the electrolyte are lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium cobalt oxide, organic lithium positive electrode, lithium-rich manganese-based positive electrode, and sulfur positive electrode.

Citation Information

Patent Citations

  • Flame-retardant electrolyte for lithium iron phosphate power cell

    CN102544581A

  • Flame-retardant electrolyte of lithium ion battery and preparation method of electrolyte

    CN107293788A